Effect of glycerol on the properties of coconut oil cake reinforced poly(lactic acid) - Sumathy Raj, Sachin; Chellapandian, Thiruvasagam; Nanjappan, Balakrishnan (Polimery, 2022)
The effect of the addition of 10-25 wt% coconut oil cake (COC) on the properties of poly (lactic acid) (PLA) was studied. PLA/COC (80/20) composite showed better mechanical properties and higher thermal stability than PLA. Glycerol used as a plasticizer further improved tensile and flexural mechanical properties, as well as the impact strength and the ability to suppress noise.